2003
DOI: 10.1046/j.1439-0310.2003.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nutrition on Courtship and Mating in the ScorpionflyPanorpa cognata(Mecoptera, Insecta)

Abstract: Scorpionflies have been used as model organisms for the study of alternative male mating tactics as well as sexual conflict and coercive mating. Here we describe the courtship and mating behaviour of the scorpionfly Panorpa cognata at different levels of nutrition. Alternative mating tactics in scorpionflies involve nuptial food gifts, and we expected an effect of nutrient availability and male individual condition on the relative frequency of these mating tactics. Subsequent to female attraction by means of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
105
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(117 citation statements)
references
References 20 publications
9
105
3
Order By: Relevance
“…In this study, the estimate of female nutritional benefits from salivary mass consumption, and thus additional matings, is in the magnitude of four or five eggs, or roughly 8%. Mean estimates of the lifetime fitness increase of polyandrous females due to salivary mass consumption, which take both the lifetime number of female matings (see Engqvist & Sauer, 2003b ) and the relative fitness increase per mating into account, would therefore be in the magnitude of slightly more than 30% for females subjected to a highly restricted diet as in the present study and approximately 20% for females in populations with ample food abundance. These estimates are thus slightly lower than the average direct benefit of multiple mating in insect species with nuptial gifts ( Arnqvist & Nilsson, 2000 ).…”
Section: How Signifi Cant Are Female Direct Benefi Ts Of Polyandry Inmentioning
confidence: 73%
See 2 more Smart Citations
“…In this study, the estimate of female nutritional benefits from salivary mass consumption, and thus additional matings, is in the magnitude of four or five eggs, or roughly 8%. Mean estimates of the lifetime fitness increase of polyandrous females due to salivary mass consumption, which take both the lifetime number of female matings (see Engqvist & Sauer, 2003b ) and the relative fitness increase per mating into account, would therefore be in the magnitude of slightly more than 30% for females subjected to a highly restricted diet as in the present study and approximately 20% for females in populations with ample food abundance. These estimates are thus slightly lower than the average direct benefit of multiple mating in insect species with nuptial gifts ( Arnqvist & Nilsson, 2000 ).…”
Section: How Signifi Cant Are Female Direct Benefi Ts Of Polyandry Inmentioning
confidence: 73%
“…The males that were used in these matings were well fed (a one-segment piece of a mealworm every third day) and between 14 and 25 days old. Furthermore, only males that were obviously emitting pheromones and thus 'calling' for females were used (see also Thornhill, 1979;Engqvist & Sauer, 2003b ). Before every mating trial, females were weighed to the nearest 0.1 mg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this species, females typically mate with multiple males (Engqvist and Sauer 2003b) and benefit in several ways from polyandry. First, female scorpionflies often receive nuptial food gifts in form of salivary secretions at mating (Mercier 1915;Byers and Thornhill 1983;Sauer et al 1998;Engqvist and Sauer 2003b;Engqvist 2006), and as showed for P. cognata, females derive nutritional benefits that increase their fecundity by consuming these gifts (L. Engqvist, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…In this species, females typically mate with multiple males (Engqvist and Sauer 2003b) and benefit in several ways from polyandry. First, female scorpionflies often receive nuptial food gifts in form of salivary secretions at mating (Mercier 1915;Byers and Thornhill 1983;Sauer et al 1998;Engqvist and Sauer 2003b;Engqvist 2006), and as showed for P. cognata, females derive nutritional benefits that increase their fecundity by consuming these gifts (L. Engqvist, unpublished data). In addition, P. cognata females benefit due to an increased egg-hatching rate by mating with different males (Engqvist 2006), possibly by avoiding genetic incompatibility (for reviews see Tregenza and Wedell 2000;Zeh and Zeh 2003;Simmons 2005).…”
Section: Introductionmentioning
confidence: 99%